Illuminating a Path4914. Copyright 2016 Wiley for Organic Synthesis Towards Sustainability. No One Said It Would Be Easy… - Lipshutz, Bruce H. (Synlett, 2021)
A personalized account is presented describing some of the stories behind the scenes in efforts to convert organic chemistry into a more sustainable discipline. These are part of a group ‘crusade’ started almost 15 years ago aimed at providing technologies illustrative of how key reactions used today can be ‘faster, better, cheaper’ when run in recyclable water. Hence, the option now exists to do organic synthesis in a far more environmentally responsible fashion. By contrast, most of organic chemistry developed over the past 200 years that relies on organic solvents continues to generate enormous amounts of pollution, while depleting finite petroleum reserves and our supplies of many precious and base metals. Making the switch to water, Nature’s chosen reaction medium, akin to that in which bio-catalysis is typically performed, is inevitable.1 The Story Begins: A Different Type of Prejudice2 Are We up to the Challenge? Too Late Now…3 ‘Impossible’ Reactive Metal Chemistry in Water4 Didn’t I Once Say: ‘It’s All about the Ligand’?5 What Happens When Our Supply of Palladium Runs Out?6 What Are the Implications from These Tales for Today and Tomorrow?7 What Is the ‘Broader Impact’ of This Work?8 The Bottom Line…
Keywords: sustainability; green chemistry; chemistry in water; chemo-catalysis; ppm level Pd